South Marmara Islands as the Center of Arms Trafficking in the Marmara Sea (1890-1914) - Burcu KURT (Gazi Akademik Bakış)
The most important of the South Marmara Islands, namely the Paşalimanı, Avşa and Ekinlik islands are in an extremely strategic point geographically because they are close to the Kapıdağ peninsula and located at the mouth of the Dardanelles. A majority of the population of the islands being non-Muslim and Greek -particularly after Greece broke away from the Ottoman state in 1829- increased the strategic importance of the region even further. In addition to grape and distillery produce, shipping to distant ports and in particular the Greek ports constituted a significant source of the island’s income. The developments that occurred in the Balkans and lack of power since the end of the 19th century in conjunction with the Greek and Armenian movements within the Ottoman Empire gave birth to a new form of illegal economy-arms trafficking-on the Marmara Islands. We see that this illegal activity intensified significantly after the Russo-Turkish War during the reign of Abdulhamid II and the Second Constitutional era. This study will be focusing on the periods of Abdulhamid II and the Second Constitution, examining the illegal arms trade, the reasons for the Marmara Islands being the center of this illegal trade, and the political and administrative initiatives of the Ottoman State to prevent this trade.